MENINGKATKAN KEPERCAYAAN DIRI MAHASISWA DALAM KEMAMPUAN PUBLIC SPEAKING DI SEKOLAH TINGGI PASTORAL KEUSKUPAN AGUNG KUPANG - Tamelab, Petrus; Ngongo, Maria Hendritha Lydia; Oetpah, Dorince (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2021)
This research aims to examine and analyze in real terms the condition of student confidence in the Pastoral College of the Archdiocese of Kupang towards public speaking skill, inhibiting factor, and effort to increase students' confidence in public speaking skill. This research uses a naturalistic descriptive approach which is a type of qualitative research method. It is called naturalistic because this research was conducted in natural conditions, while descriptive is used to show the level of explanation or process to explain the events or phenomena being studied. The data collection technique used interview question sheets which were supported by observation sheets and documentation studies. While the data analysis technique is done by collecting data, reducing data, presenting data, and making conclusions. The results showed that the students had a good level of self-confidence, and had a fairly good foundation in public speaking skills. The problem is, there is often a loss of self-confidence that hinders the ability to speak in public. This is due to lack of preparation, lack of literature references, lack of studying environmental situations, including socializing. Efforts that need to be made are learning public speaking courses not only emphasizing theory but practice or practice, it is necessary to have an open space so that students are actively involved in various activities on and off-campus in order to increase confidence in their public speaking abilities.